2022
DOI: 10.3389/fnut.2022.837719
|View full text |Cite
|
Sign up to set email alerts
|

Function Over Mass: A Meta-Analysis on the Importance of Skeletal Muscle Quality in COVID-19 Patients

Abstract: COVID-19 caused by SARS-CoV-2 infection is a highly contagious disease affecting both the higher and lower portions of the respiratory tract. This disease reached over 265 million people and has been responsible for over 5.25 million deaths worldwide. Skeletal muscle quality and total mass seem to be predictive of COVID-19 outcome. This systematic review aimed at providing a critical analysis of the studies published so far reporting on skeletal muscle mass in patients with COVID-19, with the intent of examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
3
20
0
1
Order By: Relevance
“…We were more interested in whether diagnostic parameters of sarcopenia could be the predictor of clinical outcomes after adjusting other confounders. The majority of the studies found that CT-derived body composition parameters are linked to poorer outcomes in patients with COVID-19, which is in line with recent meta-analysis findings, indicating that sarcopenia was associated with increased severity and mortality from COVID-19 ( 28 , 34 , 66 ). Ufuk et al ( 26 ) reported that pectoralis muscle area (PMA) and index (PMI) values on chest CT were significantly associated with several adverse outcomes, such as intubation, prolonged hospital stay, and death.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We were more interested in whether diagnostic parameters of sarcopenia could be the predictor of clinical outcomes after adjusting other confounders. The majority of the studies found that CT-derived body composition parameters are linked to poorer outcomes in patients with COVID-19, which is in line with recent meta-analysis findings, indicating that sarcopenia was associated with increased severity and mortality from COVID-19 ( 28 , 34 , 66 ). Ufuk et al ( 26 ) reported that pectoralis muscle area (PMA) and index (PMI) values on chest CT were significantly associated with several adverse outcomes, such as intubation, prolonged hospital stay, and death.…”
Section: Discussionsupporting
confidence: 83%
“…We were more interested in whether diagnostic parameters of sarcopenia could be the predictor of clinical outcomes after adjusting other confounders. The majority of the studies found that CT-derived body composition parameters are linked to poorer outcomes in patients with COVID-19, which is in line with recent meta-analysis findings, indicating that sarcopenia was associated with increased severity and mortality from COVID-19 (28,34,66) (29) showed that patients with low muscle mass (defined by SMI on L3 level) had a significantly higher rate of tracheostomy (50 vs. 20%, p = 0.01), prolonged ICU (adjusted HR = 0.53, 95%CI: 0.30-0.92, p = 0.024), and hospital LOS (adjusted HR = 0.50, 95% CI: 0.29-0.86, p = 0.014). Another study by Kim et al (42) also showed that baseline sarcopenia (defined by SMI on T12 level) was an independent predictor of delayed hospital discharge (adjusted hazard ratio = 0.47; 95% CI 0.23-0.96).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study demonstrated that a high IMAT index (>2.35) measured at the T12 level on chest CT was associated with high 21-day mortality in patients with COVID-19 [ 21 ]. In a meta-analysis, the presence of low muscle quality, defined as low skeletal muscle density, was associated with COVID-19 mortality, despite high heterogeneity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been closely associated with prolonged hospital stay, including ICU care and/or invasive mechanical ventilation [ 19 , 33 ] and long-standing COVID-19 syndrome [ 18 ]. However, a meta-analysis showed no association between SMI and survival rate in patients with COVID-19 [ 30 ]. In our study, sarcopenia was not associated with four-month mortality.…”
Section: Discussionmentioning
confidence: 99%